Study on Advanced Anchor - grouting Support of Mining Roadway in Close Lower Coal Seam - Lu Guozhi; Ni Ping; Li Xin; Niu Jinhua; Wang Tao (E3S Web of Conferences, 2022)
Aiming at the problems of difficult support of mining roadway under goaf of the close distance coal seam, obvious large deformation, and long-term continuous deformation of surrounding rock, an advanced bolt-grouting support system is proposed. The system can effectively solve the problem of roadway support from the design system, construction system, and monitoring and evaluation system, and realize the intelligent evaluation of bolt-grouting support. Based on the actual engineering background of 29204 working face in Dongqu Coal Mine, the supporting material and scheme, grouting parameters, and construction technology are studied and analyzed. Finally, the supporting scheme is adjusted and optimized timely by combining with the intelligent evaluation system of anchor grouting. The field practice results show that the advanced bolting-grouting support system has good applicability to roadway deformation under different conditions. The maximum subsidence of the roof in the test section is reduced by 73.48 % compared with the original support scheme, and the maximum stress of the anchor cable is reduced by 50.68 %. The research results provide a set of safe and effective support system and feasible technical ideas and methods to solve the problem of surrounding rock control of mining roadway under goaf of the close distance coal seam.